Encrypted Query Data Processing in Internet Of Things(IoTs) : CryptDB and Trusted DB - Ambika, G; Srivaramangai, P (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things (IoT) consists of two merging technologies IoT and Cloud Computing is known as IoT. In the cloud, the large amount of data might be gathered by various IoT applications. Privacy and Security concerns on behalf of IoT are proven targets of great significance. Encrypted Query Processing is securely to protect data confidentiality as preserving confidentiality and performing a standard set of SQL queries in an accurate manner for IoT. In this paper, compare the CryptDB and TrustedDB encrypted query processing systems with the purpose of IoT data stores securely in the Cloud database. The performance of an encrypted databases CryptDB and TrustedDB are compared by using SQL queries from TPCH benchmark. As a result of that TrustedDB is performed as more efficient and scalable to large datasets